Perception of Medical Health College Students Toward Mental Health (Medico Legal Update, 2020)
Background: Mental health is a major that often gets bad perception. Bad perceptions of mental healthoften occur in special populations (students). It is necessary to measure student perceptions to describe theirperceptions regarding mental healthObjective : To describe student perceptions (aspects of cognition, aspects of affection and aspects ofconation) about mental health.Method: This study uses quantitative method with descriptive approach. The sample of this study are 100college students of Public health major in UIN Alauddin, Makassar,Result: In general, cognitive aspect of respondents is positive, as well as psychomotoric and affectionaspect.Conclusion : Students’ perceptions related to mental health after measurement tend to be good for all threeaspects (cognition, affection and conation) without one statement having the largest negative percentage.